Imitating Christ in Magwi : an anthropological theology - Whitmore, Todd, 1957- (London : T&T Clark, 2019)
Imitating Christ in Magwi: An Anthropological Theology achieves two things. First, focusing on indigenous Roman Catholics in northern Uganda and South Sudan, it is a detailed ethnography of how a community sustains hope in the midst of one of the most brutal wars in recent memory, that between the Ugandan government and the rebel Lord's Resistance Army. Whitmore finds that the belief that the spirit of Jesus Christ can enter into a person through such devotions as the Adoration of the Eucharist gave people the wherewithal to carry out striking works of mercy during the conflict, and, like Jesus of Nazareth, to risk their lives in the process. Traditional devotion leveraged radical witness. Second, Gospel Mimesis is a call for theology itself to be a practice of imitating Christ. Such practice requires both living among people on the far margins of society - Whitmore carried out his fieldwork in Internally Displaced Persons camps - and articulating a theology that foregrounds the daily, if extraordinary, lives of people. Here, ethnography is not an add-on to theological concepts; rather, ethnography is a way of doing theology, and includes what anthropologists call "thick description" of lives of faith. Unlike theology that draws only upon abstract concepts, what Whitmore calls "anthropological theology" is consonant with the fact that God did indeed become human. It may well involve risk to one's own life - Whitmore had to leave Uganda for three years after writing an article critical of the President - but that is what imitatio Christi sometimes requires.
Includes bibliographical references and index.
Keywords: Jesus Christ -- Example; Christianity -- Uganda; Christianity -- South Sudan; Uganda -- Church history; South Sudan -- Church history